Analysis of Moral Values and Figurative Languages in Song Lyrics “Palestine Will Be Free” by Maher Zain - Riftasandha, Allaika; Wildan Isna Asyhar; Kristanti Yuntoro Putri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Music serves as a universal medium for conveying moral values and social messages, exemplified by Maher Zain’s song “Palestine Will Be Free.” This study addresses the gap in analyzing the moral and figurative elements of the song, focusing on its contributions to moral education and social awareness. Utilizing a qualitative research design, the study examines the song’s lyrics and integrates insights from secondary sources to identify themes of justice, freedom, optimism, solidarity, and resilience. The analysis reveals that the song employs various figurative language techniques—such as metaphors, similes, and symbolism—to deliver its moral and emotional messages effectively. For example, the metaphor “Your soul will always be free” highlights the unyielding spirit of the Palestinian people despite oppression, while the recurring theme of solidarity fosters a sense of empathy and collective responsibility. The accompanying music video further amplifies the da'wah message, showcasing visuals of patience, faith, and hope in adversity. These findings affirm the song’s dual role as an artistic expression and a platform for moral advocacy, resonating with broader discussions on music’s potential to inspire ethical consciousness and social change. However, the study’s focus on lyrical and figurative analysis limits its scope, as it does not delve into the sociopolitical context or audience reception. Future research should explore these aspects, including cross-cultural interpretations and empirical studies on listener responses, to provide a deeper understanding of the song’s global impact.